Pollinator habitat enhancement through ornamental plants, floral traits and urban green area features for planning biodiversity-friendly cities - Paolo Biella; Giulia Brambilla; Valentina Verduci; Matteo Annessi; Andrea Beltramini; Lorenzo Bianco; Daniele Calabrese; Francesca Romana Dani; Marta Depetris; Andrea Di Giulio; Andrea Ferrari; Jessica Frigerio; et al. (Landscape and Urban Planning, 2026)

Variation in pollinator assemblage along a Mediterranean urbanization gradient does not affect the reproductive output of the wild radish - Carla Sorvillo; Paolo Biella; Giulia Brambilla; Massimo Labra; Salvatore Cozzolino; Giovanni Scopece (Urban Ecosystems, 2026)

The role of urban forests in tackling air and soil pollution in Italian cities - Barbara Baesso Moura; Werther Guidi Nissim; Jacopo Manzini; Andrea Scartazza; Massimo Labra; Yasutomo Hoshika; Pierre Sicard; Alessandro Zaldei; Alessandra De Marco; Elena Paoletti (Urban Forestry & Urban Greening, 2025)

Plant identification in the era of digitalization: opportunities and challenges - Jessica Frigerio; Emily Rose Palm; Giovanni Zecca; Valentina Verduci; Werther Guidi Nissim; Fabrizio Grassi; Massimo Labra (Plant Biosystems, 2025)

Modelling the environmental implications of phytoremediation in urban settings: A review of the integration of life cycle assessment and ecosystem services approaches - Lidia Favaretto; Benedetto Rugani; Carlo Calfapietra; Massimo Labra; Werther Guidi Nissim (Urban Forestry & Urban Greening, 2025)

Biodiversity-friendly practices to support urban nature across ecosystem levels in green areas at different scales - Paolo Biella; Luciano Bani; Enrico Caprio; Francesca Cochis; Olivia Dondina; Valentina Fiorilli; Andrea Genre; Rodolfo Gentili; Valerio Orioli; Rosa Ranalli; Pietro Tirozzi; Massimo Labra (Urban Forestry & Urban Greening, 2025)

Forest spatial configuration and local management influence bee pollinator biodiversity in urban and rural landscapes - Rosa Ranalli; Andrea Galimberti; Massimo Labra; Paolo Biella (Journal of Environmental Management, 2025)

Lawn management promoting tall herbs, flowering species and urban park attributes enhance insect biodiversity in urban green areas - Paolo Biella; Sara Borghesan; Beatrice Colombo; Andrea Galimberti; Lorenzo Guzzetti; Davide Maggioni; Emiliano Pioltelli; Fausto Ramazzotti; Rosa Ranalli; Nicola Tommasi; Massimo Labra (Urban Forestry & Urban Greening, 2025)

Vineyard footprint on pollinators is mediated by flower vegetation, organic farming, seasonal and weather factors, a case study from North Italy - Paolo Biella; Fausto Ramazzotti; Giulia Parolo; Andrea Galimberti; Massimo Labra; Mattia Brambilla (Agriculture, Ecosystems & Environment, 2025)

Antibiotic resistance in urban soils: Dynamics and mitigation strategies - Annamaria Gentile; Luca Di Stasio; Gianmaria Oliva; Giovanni Vigliotta; Angela Cicatelli; Francesco Guarino; Werther Guidi Nissim; Massimo Labra; Stefano Castiglione (Environmental Research, 2024)

Land use influences the nutrient concentration and composition of pollen and nectar rewards of wildflowers in human-dominated landscapes - Emiliano Pioltelli; Lorenzo Guzzetti; Malika Ouled Larbi; Rita Celano; Anna Lisa Piccinelli; Andrea Galimberti; Paolo Biella; Massimo Labra (Science of The Total Environment, 2024)

DNA metabarcoding unveils the effects of habitat fragmentation on pollinator diversity, plant‐pollinator interactions, and pollination efficiency in Maldive islands - Nicola Tommasi; Paolo Biella; Davide Maggioni; Luca Fallati; Giulia Agostinetto; Massimo Labra; Paolo Galli; Andrea Galimberti (Molecular Ecology, 2023)
Habitat fragmentation affects biodiversity, but with unclear effects on pollinators and their interactions with plants in anthropized landscapes. Islands could serve as open air laboratories, suitable to disentangle how land‐use alteration impacts pollination ecology. In Maldive islands we investigated how pollinator richness, plant‐pollinator interactions and pollination efficiency are influenced by the green area fragmentation (i.e., gardens and semi‐natural patches). Moreover, we considered the mediating role of pollinator body size and the plant trait of being invasive in shaping interactions. To do this, we surveyed pollinator insects from 11 islands representing a gradient of green area fragmentation. A DNA metabarcoding approach was adopted to identify the pollen transported by pollinators and characterize the plant‐pollinator interactions. We found that intermediate levels of green area fragmentation characterized pollinator communities and increased their species richness, while decreasing interaction network complexity. Invasive plants were more frequently found on pollinator bodies than native or exotic noninvasive ones, indicating a concerningly higher potential for pollen dispersal and reproduction of the former ones. Intriguingly, pollinator body size mediated the effect of landscape alteration on interactions, as only the largest bees expanded the foraging diet in terms of plant richness in the transported pollen at increasing fragmentation. In parallel, the pollination efficiency increased with pollinator species richness in two sentinel plants. This study shows that moderate landscape fragmentation of green areas shapes many aspects of the pollination ecosystem service, where despite interactions being less complex and mediated by pollinator body size, pollinator insect biodiversity and potential plant reproduction are supported.

Tree tracking: species selection and traceability for sustainable and biodiversity-friendly urban reforestation - Jessica Frigerio; Giulia Capotorti; Eva Del Vico; Malika Ouled Larbi; Fabrizio Grassi; Carlo Blasi; Massimo Labra; Werther Guidi Nissim (Plant Biosystems, 2023)

Effect of urbanization and its environmental stressors on the intraspecific variation of flight functional traits in two bumblebee species - Nicola Tommasi; Emiliano Pioltelli; Paolo Biella; Massimo Labra; Maurizio Casiraghi; Andrea Galimberti (Oecologia, 2022)
The way urbanization shapes the intraspecific variation of pollinator functional traits is little understood. However, this topic is relevant for investigating ecosystem services and pollinator health. Here, we studied how urbanization affects the functional traits of workers in two bumblebee species ( Bombus terrestris and B. pascuorum ) sampled in 37 sites along a gradient of urbanization in North Italy (an area of 1800 km 2 including the metropolitan context of Milan and other surrounding capital districts). Namely, we investigated the effect of land use composition, configuration, air temperature, flower resource abundance, and air pollutants on the variation of traits related to flight performance and of stress during insect development (i.e., wing size, wing shape and size fluctuating asymmetry). The functional traits of the two bumblebees responded idiosyncratically to urbanization. Urban temperatures were associated with smaller wing sizes in B. pascuorum and with more accentuated fluctuating asymmetry of wing size in B. terrestris . Moreover, flower abundance correlated with bigger wings in B. terrestris and with less asymmetric wing size in B. pascuorum . Other traits did not vary significantly, and other urban variables played minor effects. These species-specific variation patterns highlight that environmental stressor linked to urbanization negatively impact the traits related to flight performance and development stability of these syntopic bumblebees, with possible consequences on the pollination service they provide.

Artichoke ( Cynara cardunculus var. scolymus L.) by-products as a source of inulin: how to valorise an agricultural supply chain extracting an added-value compound - Sofia Cavini; Lorenzo Guzzetti; Francesca Givoia; Maria Elena Regonesi; Patrizia Di Gennaro; Chiara Magoni; Luca Campone; Massimo Labra; Ilaria Bruni (Natural Product Research, 2022)

Using Glycerol to Produce European Sea Bass Feed With Oleaginous Microbial Biomass: Effects on Growth Performance, Filet Fatty Acid Profile, and FADS2 Gene Expression - Genciana Terova; Federico Moroni; Micaela Antonini; Stefano Bertacchi; Chiara Pesciaroli; Paola Branduardi; Massimo Labra; Danilo Porro; Chiara Ceccotti; Simona Rimoldi (Frontiers in Marine Science, 2021)
Using a circular economy concept, the present study investigated the use of crude glycerol, a primary by-product of biodiesel production, as a low-priced nutrient source for heterotrophic cultivation of the fungus-like protist Schizochytrium limacinum SR21 strain. The whole biomass of this oleaginous microorganism, rich in docosahexaenoic acid (DHA) and high-quality proteins, was then paired with a vegetable oil (VO) source and used to replace fish oil (FO) in European sea bass ( Dicentrarchus labrax ) feeds. Four nutritionally balanced diets were formulated: diet FO (a FO-based diet), diet VO + 0 (a VO-based diet without S. limacinum ), and diets VO + 5 and VO + 10 that were VO-based feeds supplemented with 5 and 10% of S. limacinum , respectively. After a 3-month feeding trial, fish of all dietary groups tripled their initial weight, but growth and feeding efficiencies of D. labrax were not significantly different among treatments. Although the formulated diets were balanced for polyunsaturated fatty acids (PUFAs), fish fed with feeds containing either VO or VO plus 5 and 10% of S. limacinum biomass had significantly higher levels of PUFAs in the flesh than fish fed the FO-based diet. Values of health-related lipid indexes, such as atherogenicity index, thrombogenicity index, and flesh lipid quality as well as n-6/n-3 and PUFAs/SFAs ratios confirmed the high nutritional value of sea bass filet, thus representing a healthy product for human consumption. Although the PUFAs/SFAs ratio showed a significantly higher value in fish fed with VO-based diets supplemented with S. limacinum than in those fed with FO diet, suggesting a better filet quality, the n-6/n-3 ratio clearly indicated that filet quality of dietary group FO was best (value of 0.55) and that of group VO + 10 second best (value of 0.98). We also evaluated the nutritional regulation of Δ6-desaturase (or fads2 ) gene expression in European sea bass liver. European sea bass fed the VO + 0 diet had the highest number of mRNA copies for Δ6-desaturase (or fads2 ), fish fed with diet VO + 10 the lowest. Our study adds to the growing body of literature concerning the use of thraustochytrid biomass as a valid alternative to marine-derived raw materials for European sea bass feeds.

Investigating pollination strategies in disturbed habitats: the case of the narrow-endemic toadflax Linaria tonzigii (Plantaginaceae) on mountain screes - Paolo Biella; Asma Akter; Antonio Jesús Muñoz-Pajares; Germano Federici; Andrea Galimberti; Jana Jersáková; Massimo Labra; Federico Mangili; Nicola Tommasi; Luca Mangili (Plant Ecology, 2021)
Plant mating systems may reflect an adaptation to a habitat type, with self-pollination being potentially common in unstable and disturbed conditions. We investigated the reproductive ecology of an Alpine, narrow-range toadflax, Linaria tonzigii Lona (Plantaginaceae), occurring in steep and dynamic mountain screes. We explored self-compatibility and spontaneous autogamy, seed viability, daily nectar production, pollinator behaviour and pollen transfer in wild populations, using hand pollination treatments, quantification of nectar volume, viability Tetrazolium assay, active pollinator sampling and video recordings, and UV-bright dust for pollen substitution. After ex novo sequencing of several genetic regions of L. tonzigii , we performed a multi-marker phylogenetic analysis of 140 Linaria species and tracked the occurrence of the self-compatibility trait. Our results showed that this species is self-compatible, pollinated mostly via spontaneous autogamy and pollinator-mediated geitonogamy, and self-pollinated seeds are as viable as cross-pollinated ones. Selfing could be due to pollinator rarity because, despite the studied species providing a high nectar volume, wild bees, moths and small beetles infrequently visited its flowers in the sparsely vegetated scree slopes. In addition, a preliminary survey showed a low genetic haplotype diversity in the study plant. Moreover, the phylogeny shows that self-compatibility is scattered in the tree, suggesting the adaptive nature of this reproductive trait in the genus Linaria . This study supports for theories that high prevalence of selfing is an adaptation to environments unfavourable for cross-pollination, and particularly where pollinators are rare, such as in perturbed, poorly vegetated high-elevation habitats.

Identifying population thresholds for flowering plant reproductive success: the marsh gentian (Gentiana pneumonanthe) as a flagship species of humid meadows and heathland - Simon Pierce; Alberto Spada; Elisabetta Caporali; Filippa Puglisi; Andrea Panzeri; Alessandra Luzzaro; Simona Cislaghi; Lia Mantegazza; Elisa Cardarelli; Massimo Labra; Andrea Galimberti; Roberta M. Ceriani (Biodiversity and Conservation, 2018)

Chemical, molecular, and proteomic analyses of moss bag biomonitoring in a petrochemical area of Sardinia (Italy) - Pierluigi Cortis; Candida Vannini; Annalena Cogoni; Fabrizio De Mattia; Marcella Bracale; Valerio Mezzasalma; Massimo Labra (Environmental Science and Pollution Research, 2016)

Pea seed extracts stimulate germination of the terrestrial orchid Ophrys apifera Huds. during a habitat restoration project - Simon Pierce; Valentina Guidi; Andrea Ferrario; Roberta M. Ceriani; Massimo Labra; Ilda Vagge; Bruno E. L. Cerabolini (Plant Biosystems, 2015)

Genetic variability of relict Rhododendron ferrugineum L. populations in the Northern Apennines with some inferences for a conservation strategy - Ilaria Bruni; Fabrizio De Mattia; Massimo Labra; Fabrizio Grassi; Silvia Fluch; Maria Berenyi; Carlo Ferrari (Plant Biosystems, 2012)

The Combined Toxic and Genotoxic Effects of Chromium and Volatile Organic Contaminants to Pseudokirchneriella subcapitata - Massimo Labra; Fabrizio De Mattia; Marzia Bernasconi; Daniela Bertacchi; Fabrizio Grassi; Ilaria Bruni; Sandra Citterio (Water, Air, & Soil Pollution, 2010)

Study of genetic relationships between wild and domesticated grapevine distributed from Middle East Regions to European countries - Fabrizio De Mattia; Serena Imazio; Fabrizio Grassi; Hamed Doulati Baneh; Attilio Scienza; Massimo Labra (Rendiconti Lincei. Scienze Fisiche e Naturali, 2008)

Chloroplast and nuclear DNA markers to characterize cultivated and spontaneous Ribes - Fabrizio de Mattia; Fabrizio Grassi; Serena Imazio; Massimo Labra (Plant Biosystems, 2008)

Antibiotic-induced DNA methylation changes in calluses of Arabidopsis thaliana - Mauro Bardini; Massimo Labra; Mark Winfield; Francesco Sala (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

Methylation changes in specific sequences in response to water deficit - Massimo Labra; Candida Vannini; Marcella Bracale; Francesco Sala (Plant Biosystems, 2002)

Isolation and characterization of two cyclin cDNAs from Pisum sativum L. - Massimo Labra; Sandra Citterio; Alessandra Ghiani; Elisabetta Onelli; Silvia Barbesti; Sergio Sgorbati (Plant Biosystems, 2001)

The presence of a p53-like protein during pea seed maturation and germination - Elisabetta Onelli; Sandra Citterio; Massimo Labra; Alessandra Ghiani; Sergio Sgorbati (Plant Biosystems, 2000)